What Do We Know about the Internationalization of Central and Eastern European Countries and Firms? - Wiliński, Witold (Comparative Economic Research. Central and Eastern Europe, 2013)
This article is the first comprehensive literature review concerning the internationalization of countries and firms from Central and Eastern European countries (CEECs). The study covers 42articles published during the years 1989-2010, both in leading world journals on international business and management and in regional journals concentrating on the CEECs. The purpose of the study is classification of the research topics undertaken, defining the differences in internationalization between CEECs, and verification whether the studies on outward FDI from CEECs has made an important contribution to international business theory.